ECONOMICS OF GILL NETTING AND TWO BOAT MID WATER TRAWLING - SADANANDAN, K A; KARTHA, K N; GEORGE, T P; IYER, H KRISHNA (Fishery Technology, 2017)
The paper deals with the economic aspects of operation of gill netting and two boat midwater trawling conducted off Cochin The data collected on two boat midwater trawling and gill netting during 1979 and 1980-81 are presented. Gin netting was profitable at the range of 17.5 and 25.2 % while two midwater trawling was profitable at the rate of 18.5 %.